Strategies to Improve Discipline for Educators At Al Mubarok Kindergarten - Wahab, Aulia Dwi Amalina; Silfiya; Salma Fathia (Islamic EduKids: Jurnal Pendidikan Anak Usia Dini, 2024)
Educators play an important role in the implementation of education in schools to shape student character and achieve educational success. One way that educators need to do this is the ability to manage time effectively. This research aims to identify the factors that cause teacher tardiness at Al-Mubarok Kindergarten and develop strategies to improve time discipline. This research uses a qualitative descriptive method, with data collection techniques through observation and in-depth interviews. Observations were carried out to observe teacher tardiness and its impact on student activities in class. In-depth interviews were conducted with teachers and parents of students to dig deeper into the reasons for tardiness. The research results show that teacher tardiness not only disrupts the learning process, but also influences student behavior, who tend to become restless and lack discipline. Teachers stated that personal responsibilities at home were the main factor in their tardiness. As a solution, schools are advised to enforce stricter time discipline rules and provide time management training for teachers. It is hoped that increasing time discipline can improve the quality of learning and provide a positive role model for students, thereby creating a more conducive learning atmosphere at Al-Mubarok Kindergarten.   Keywords: Strategy, Educator, Discipline, Learning.